Outcomes of remnant‐preserving anterior cruciate ligament reconstruction using Achilles tendon allografts: A retrospective analysis of tibial tunnel widening and complications - Siyeon Kim; Dae Keun Suh; Dong Won Suh (Journal of Experimental Orthopaedics)
Abstract Purpose This study evaluates the outcomes of remnant‐preserving Anterior cruciate ligament reconstruction (ACLR) using Achilles tendon allografts, focusing on tibial tunnel widening and complications. The primary research question is whether this technique results in significant tunnel widening and other complications. Methods We performed a retrospective analysis of 396 patients who underwent ACLR with Achilles tendon allografts between 2010 and 2023. Magnetic resonance imaging (MRI) scans were taken post‐operatively and at follow‐up, with tunnel width measured at both time points. Tunnel width was measured perpendicular to the tunnel's long axis, assessing both anteroposterior and mediolateral dimensions, 1 cm distal to the articular surface. The cross‐sectional area (CSA) of the tibial tunnel was calculated by multiplying the two measured widths. Statistical analysis included paired t tests and linear regression to assess factors affecting tibial tunnel widening. Results Follow‐up MRI scans of 179 patients showed a non‐significant increase in the tibial tunnel CSA of 3.49 mm2 (p = 0.08). However, 45.2% of patients had a decrease in CSA. A statistically significant correlation was found between the time interval between MRI scans and CSA changes, with a decrease in CSA of 0.195 mm2 per month (p = 0.007). Graft failure occurred in 5.3% of patients, and 2% required additional surgery for meniscal or cartilage damage. Cyclops lesions were identified in six patients and were treated surgically. Conclusion This study demonstrates that remnant‐preserving ACL reconstruction using Achilles tendon allografts does not lead to significant tibial tunnel widening and has low complication rates, indicating that it is a safe and effective technique. Level of Evidence Level IV, case series.